Can University Students' Beliefs Mediate the Link between Dark Triad Traits and Academic Dishonesty? - A. Ivan; M. Pavalache-Ilie (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
This article presents the mediating role of Academic Entitlement on the relationship between the Dark Triad personality traits (e.g. psychopathy, Machiavellianism and narcissism) and students' engagement in unethical academic behaviours (e.g. plagiarism, cheating). The study included 155 students enrolled in various universities across Romania. These findings indicate that externalized responsibility was the only factor which mediate the relationship between Dark Triad traits and Academic Dishonesty.